Factors Affecting the Meaning of Life in Breast Cancer Patients at Malang City, Indonesia - Supriati, Lilik; Nova, Renny; Ahsan, Ahsan; Rodli, Muhammad; Rismayanti, I Dewa Ayu; Kapti, Rinik Eko (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
The meaning of life is considered to affect breast cancer patients positively. Finding meaning in life is key to improving well-being during and after experiencing a traumatic event such as cancer. Previous research was still rare to explore the factors affecting the meaning of life in breast cancer patients. The study aimed to analyze the factors influencing the meaning of life of breast cancer patients. This study was an analytical observational method with a cross-sectional design. The inclusion criteria of the respondents were breast cancer patients who had obtained at least one cycle of chemotherapy. We used purposive sampling, and the total sample in this study was 135 respondents. Questionnaires were used to collect the data. Data were analysed by multivariate test, namely a linear regression test with a significance level of p ≤ 0,05. The result showed only two variables affect the meaning of life, communication of health workers and spirituality, respectively. The strongest variable was the communication of health workers. The equation from the analysis showed that 11 % explained the phenomenon. The spirituality and communication of health workers positively affected the meaning of life. Application of therapeutic communication as well as spiritual support are needed in nurses to patients while undergoing therapy. Therefore, nurses must pay attention to spirituality and good therapeutic communication when providing patient services.